Clopidogrel Loading Dose 300 vs. 600 mg in Patients Undergoing One-Stop Hybrid Coronary Revascularization: A Prospective Single-Center Randomized Pilot Study - Guo, Yulin; Li, Dongjie; Gao, Yingdi; Zhao, Jing; An, Xiangguang; Liu, Yan; Gu, Song; Zhang, Xitao; Gao, Jie; Su, Pixiong (Frontiers in Surgery, 2021)
Background: The optimal loading dose of clopidogrel in one-stop hybrid coronary revascularization (HCR) remains an “evidence-free” zone. This study aimed to compare the major bleeding and ischemic thrombotic events between different clopidogrel loading doses (300 mg versus 600 mg) in one-stop HCR. Methods: In this prospective, single-center, randomized, parallel, pilot study, 100 patients receiving one-stop HCR were randomly assigned to the clopidogrel loading dose 300-mg group or 600-mg group in a 1:1 ratio. Major bleeding events and composite in-hospital ischemic thrombotic and adverse complications were evaluated after the procedure. Results: postoperative mean chest drainage of fist four days and total drainage were comparable between the two groups. No differences were found in Bleeding Academic Research Consortium (BARC) coronary artery bypass grafting (CABG) related bleeding (4.0% vs. 2.0%, P = 1.00), PLATelet inhibition and patient Outcomes (PLATO) life-threatening bleeding (20.0% vs. 26.0%, P = 0.48) and PLATO major bleeding (70.0% vs. 76.0%, P = 0.50) in the two groups. The composite ischemic thrombotic and adverse events were also similar. Conclusions: In patients receiving one-stop HCR, clopidogrel 600 mg loading dose did not increase major bleeding events compared with 300 mg. More sufficient data is requisite to evaluate the potential benefits of 600 mg loading dose in one-stop HCR.